2022
DOI: 10.3390/land11050733
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Public Support for European Protected Areas: A Review of the Literature and Proposing a New Approach for Policy Makers

Abstract: Protected Areas are the most widely applied policy tool for biodiversity conservation. In Europe, protected areas are expected to significantly increase as the new EU Biodiversity strategy sets an ambitious target of 30% of land and 30% of water to be protected by 2030. Despite the popularity of this environmental policy, understanding variations in the level of public support for protected areas remains underexplored. This is an important area of research, considering that, in order for protected areas to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…The structured questionnaire was initially created based on a literature review regarding which factors have been identified as potential determinants of public support (see Jones et al 2022) and was then translated with the support of park authorities to ensure that all questions were meaningful for the local participants. Below we describe the selection of the main indicators included in our analysis (see also table 2):…”
Section: Description Of Sample and Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…The structured questionnaire was initially created based on a literature review regarding which factors have been identified as potential determinants of public support (see Jones et al 2022) and was then translated with the support of park authorities to ensure that all questions were meaningful for the local participants. Below we describe the selection of the main indicators included in our analysis (see also table 2):…”
Section: Description Of Sample and Questionnairementioning
confidence: 99%
“…responsible environmental behaviour when using the PA) (Jones et al 2022). A mosaic of factors have been proposed aiming to explain the level of support for PAs ranging from sociodemographic characteristics to governance aspects (Carrus et al 2005, Fiall and Jacobson 2009, Bennett et al 2019, Jones et al 2022. Contributions from behavioural sciences emphasize that it is mainly individual factors that influence the level of stated and active support for environmental policies (Ajzen 1985, Stern et al 1999.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their role as multi-functional landscapes, PAs may have a very wide range of positive and negative social impacts and may impact on different stakeholders according to their geographical location, as well as depending on the influence of diverse social factors [7][8][9][10]. The magnitude and direction of the impact (positive or negative) will therefore depend 2 of 19 significantly on the stakeholder group and type of user.…”
Section: Introductionmentioning
confidence: 99%
“…However, new regulations accompanying the designation of a PA often restrict local communities' practices and livelihoods due to changes in governance, ownership rights, and access to natural resources [11,12]. Public perception of such impacts, positive and negative, are found to be a key factor affecting public support for nature protected areas [8][9][10]13], and the assessment and equitable management of such impacts will be essential for the legitimacy of PAs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%